A new technology for pacifier weaning: a thematic analysis - Al Hariri, Ahmed (Frontiers in Pediatrics, 2023)
Babies and toddlers often become accustomed to using baby pacifiers. However, pacifiers may harm children’s health and lead to various problems, such as less frequent breastfeeding, shorter breastfeeding duration, dental deformities, tooth decay, recurrent acute otitis media, sleep disorders, and the potential for accidents. This study aims to introduce new technology that may prevent babies from becoming used to a pacifier (patent titled ‘Prevents Getting Used to Pacifier Baby, Number SA10609, Saudi Authority for Intellectual Property’). This study used a descriptive qualitative design. The participants included three pediatricians, three psychologists, three dentists, three family doctors, and three mothers of babies and toddlers, with a mean age of 42.6 years old (SD = 9.51). Semi-structured interviews were used, and thematic analysis was conducted to generate a thematic tree. The thematic analysis resulted in three themes: (1) the disadvantages of pacifier use, (2) the introduction of new technology for the patent, and (3) the expectations for this technology. The results showed that a pacifier might negatively affect the health of babies and toddlers. However, the new technology may prevent children from becoming used to pacifiers and protect them from any possible physical or mental issues.